Aortic Valve Bioprostheses: Leaflet Immobility and Valve Thrombosis. Issue 18 (2nd May 2017) - Holmes, David R.; Mack, Michael J.
Abstract : Leaflet immobility and valve thrombosis have been reported with both transcatheter and surgical aortic valve bioprostheses. The relationships between these abnormalities and their incidence, time course, clinical significance, predisposing factors, optimal imaging modality, and current therapeutic options remain uncertain but are rapidly evolving. Four-dimensional computerized tomographic imaging has been determined to have the highest sensitivity in studies evaluating leaflet immobility and valve thrombosis. Echocardiography is also used during surveillance, but it appears to be less sensitive. The definitive diagnosis of valve thrombosis is based on a combination of diagnostic 4-dimensional computerized tomographic imaging findings, resolution of imaging abnormalities, and elevated transcatheter gradients with anticoagulation or surgical or pathological confirmation. Uncertainty about the incidence and clinical significance of the findings is the basis of 2 US Food and Drug Administration–approved studies comparing transcatheter and surgical aortic valve replacement with a subset undergoing surveillance 4-dimensional computerized tomographic imaging. Given the expansion of transcatheter aortic valve procedures, including potentially lower-risk patients, the resolution of these uncertainties is critical.